An Integrative Model of an Artificial Intelligence (AI) Based Smart Legal Platform for the Protection of Creative Workers in Indonesia’s Digital Economy Era - Marlia Hafny Afrilies; Yuris Tri Naili; Angie Angel Lina (Universitas Trunodjoyo Madura, 2026)
The rapid growth of Indonesia’s creative economy, driven by digital transformation, has created unprecedented opportunities for creative workers, while simultaneously leaving them legally vulnerable. This includes unclear employment status, inadequate contractual arrangements, and limited access to legal and social protection. This research develops an integrative model of an Artificial Intelligence (AI), powered Smart Legal Platform to strengthen legal protection for creative workers in the digital economy. Using a mixed normative-empirical research approach, the study combines legal analysis of labor regulations, intellectual property, and social security with field data from 30 creative workers across various digital subsectors. Quantitative data were analyzed using validity and reliability tests, while qualitative insights were obtained from structured interviews and focus group discussions (FGDs). The proposed platform integrates four key features: AI-based legal consultation, automated contract creation, online dispute resolution, and integration with the national social security service (BPJS). Findings indicate a high demand for AI-based legal solutions, with respondents emphasizing the need for a platform that is accessible, affordable, and easy to use. The proposed model contributes theoretically to the debate on AI use in law and practically offers a scalable, modular, and inclusive legal technology solution for the creative sector. Its implications extend to policymakers, platform managers, and the broader digital labor market, in line with achieving Sustainable Development Goals (SDGs) 8 and 16.